Fetomaternal outcome in fibroid complicating pregnancy: a retrospective study - Sankaran, Suneela Mullakkal; Pillai, Jayasree Sukumara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Fibroids are the commonest benign tumour arising from the smooth muscle from uterus. Effects of fibroids on pregnancy and the effects of pregnancy on fibroids are a frequent clinical concern since these tumors are common in women of reproductive age. Most pregnant women with fibroids do not have any complications during pregnancy related to the fibroids. Pain is the most common problem and there may be a slightly increased risk of obstetrical complications like miscarriage, preterm labor and delivery, malpresentation and placental abruption. Methods: A retrospective study was carried out to study the fetomaternal complications in fibroid complicating pregnancies. Duration of study period was one year. Study was from 1 January 2019 to 31 December 2019 in government medical college, Kozhikode. Patients beyond 28 weeks of gestational age with fibroid complicating pregnancies were included. Case records were reviewed from medical records library government medical college, Kozhikode. Detailed review of patients including history, examination and ultrasound scan reports, mode of delivery, antepartum, intrapartum, postpartum complications and details of babies were also taken. Results: During the study period a total of 112 cases of fibroid complicating pregnancies were included in the study out of 15875 total number of deliveries. Majority of patients belonged to age group between 30 to 35 years (40.17%) and 28.1% belonged to between 35 and40 years. 63.39% of patients were multies. In most of the cases fibroid was diagnosed by the first trimester ultra sound itself. Size of uterus remained corresponding to gestational age in more than half of cases (56.25%). There was increased incidence of caesarean delivery (56.25%), preterm delivery (7.2%) and placenta praevia (2.8%) postpartum haemorrhage (10.71%) in the studied cases. Conclusions: Fibriod complicating pregnancies are associated with higher incidence of obstetric complications during all the phases of pregnancy. Proper antenatal care and assessment can reduce the adverse outcomes to a greater extent.